Vital signs continuously monitored by two wearable devices in pediatric oncology patients, NCT04914702 - Lukas Farner; Christa König; Jochen Rössler; Christine Schneider; Johanna Wyss; Roland A. Ammann; Eva Brack (Scientific Data)
Abstract Continuous temperature monitoring with wearable devices may lead to earlier fever detection. This may improve the outcome of fever in neutropenia episodes in pediatric patients with cancer. This prospective two-center observational and proof-of-concept study recruited pediatric patients undergoing chemotherapy for cancer. Two different wearable devices (WDs), the CORE® and the Everion®, were worn for 14 days to continuously record multiple vital signs. Both WDs record core temperature and its quality score. Everion® records 17 further vital signs or health scores. All measurements resulted in 4945 (CORE®) and 5360 hours (Everion®) of data. Combined, 6’085’943 measurements of vital signs and health scores were recorded. In addition, non-WD data such as acceptability, side effects and discrete ear temperature measurements were collected. The described methods and resulting data can be reused to study acceptability, usability, compliance, and data quality of the CORE® and Everion® devices in pediatric patients. Additionally, these methods and data can be utilized to study vital signs in pediatric patients undergoing chemotherapy for cancer.